Erythrocyte, Hemoglobin, and Hematocrit Profiles in Indonesian Simental and Limousin in Highlands and Lowlands in Banyuwangi - Sharfina Habibah Trisnawati; Erma Safitri; Bodhi Agustono; Epy Muhammad Luqman; Amung Logam Saputro; Ragil Angga Prastiya (Journal of Basic Medical Veterinary, 2025)
This study aimed to evaluate the differences in blood profile of erythrocytes, hemoglobin, and PCV in Indonesian simental and limousin beef cattle in highlands and lowlands. Banyuwangi is one of the beef cattle contributors in East Java with its highland and lowland topography. This research was conducted from July to August 2023. The research was conducted in 3 locations namely highlands (Kalibaru), lowlands (Rogojampi) and sample examination in Airlangga University Banyuwangi. Animals used in this study were Indonesian simental and limousin beef cattle with 1-2 years of age as many as 15 heads in the highlands and 15 heads in the lowlands. The research method used was purposive sampling. Blood samples used in this study used Indonesian simental and limousin beef cattle blood taken using venoject and inserted in EDTA tubes and examined using a Hematology Analyzer. The variables observed in this study were the number of erythrocytes, hemoglobin, and PCV. The data obtained were processed with Independent T-test data analysis. The results showed no significant difference in erythrocytes and PCV, but there was a significant difference in hemoglobin levels. The conclusion of this study is that Indonesian simental and limousin beef cattle in the lowlands experience mild anemia.